Performance analyses of coherent fast FHSS/MPSK systems over non-fading and fading channels with partial band noise jamming and AWGN - Kang, Jin Jun. (2008)
In this thesis, the bit error rate performance analyses of a coherent fast frequency-hopped spread-spectrum system in the presence of partial band noise jamming and additive white gaussian noise were extended from one hop per signaling interval to multiple hops per signaling interval.